ANALISIS KUALITAS PELAYANAN DALAM PEMBUATAN IZIN MENDIRIKAN BANGUNAN PADA DINAS PENANAMAN MODAL PELAYANAN TERPADU SATU PINTU KABUPATEN PESISIR BARAT - Jamal Jamal; Herti Putri Yana (e-JKPP, 2019)
The problems in this research are: (1) How is the quality of service in making building permits at the One Stop Investment Service, Pesisir Barat Regency. (2) What aspects support and hinder the quality of services in making building permits at the One Stop Investment Service, Pesisir Barat Regency.The research method used in this research is to use qualitative research with descriptive analysis method. The use of this method is to study and describe qualitatively, how is the quality of service in making building permits at the One Stop Investment Service, Pesisir Barat Regency. All data were obtained directly from informants in the field using interview and observation techniques, according to the research objectives to be achievedThe results showed that the measurement of service quality variables in the making of building permits at the One Stop Investment Service, Pesisir Barat Regency. Shows that, it has been implemented, but not optimal, this is due to (1) Relatively lack of officers who supervise and socialize the building permit management program, because the work area is so wide that it is difficult to reach all of these areas (2) there is no public awareness to take care of a building permit before building a house, so that the number of buildings that have a building permit is still relatively small, even then only around the city center that takes care of building permits.